Macroeconomic and Price of Oil and Gold on Liabilities of Hajj Fund Management Agency - Sulistyowati, Lilies; Hamzah, Muhammad Zilal; Ratnawati, Nirdukita (Pandawan, 2025)
This study examines the influence of macroeconomic variables on the sustainability of hajj funds managed by the Indonesian Hajj Financial Management Agency (BPKH). Using monthly data from 2019-2023, the research employed multiple linear regression analysis followed by dynamic systems modeling to assess fund sustainability. The regression results show that GDP growth and exchange rates positively influence hajj fund assets (p<0.05), while BI-7 Day Reverse Repo Rate, inflation, and Jakarta Islamic Index negatively affect fund assets. Dynamic system simulations reveal that under current conditions (ROI 6.78%, subsidy portion 40%), hajj funds will face deficit by 2030. However, optimistic scenarios with increased ROI to 10% and reduced subsidy portions to 20% ensure fund sustainability until 2050, with assets reaching IDR 569 trillion. These findings suggest that BPKH should enhance investment portfolio returns while the government should reconsider subsidy allocation policies to ensure long-term sustainability of hajj fund management in Indonesia.